2021
DOI: 10.1152/physiolgenomics.00140.2020
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic transcriptional profile reveals the role of diet and genetic backgrounds on metabolic traits in female progenitor strains of the Collaborative Cross

Abstract: Mice have provided critical mechanistic understandings of clinical traits underlying Metabolic Syndrome (MetSyn) and susceptibility to MetSyn in mice is known to vary among inbred strains. We investigated the diet- and strain-dependent effects on metabolic traits in the eight Collaborative Cross (CC) founder strains (A/J, C57BL/6J, 129S1/SvImJ, NOD/ShiLtJ, NZO/HILtJ, CAST/EiJ, PWK/PhJ, and WSB/EiJ). Liver transcriptomics analysis showed that both atherogenic diet and host genetics have profound effects on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 103 publications
(113 reference statements)
0
5
0
Order By: Relevance
“…The MGI and Wellcome Sanger Institute provide sequencing data of most of the inbred strains, including the eight CC founder strains. As a preliminary study, we analyzed the liver transcriptomes of eight CC founder strains fed a high-fat cholesterol diet and found that the NOX4, which is associated with hepatic triglyceride and plasma trimethylamine N-oxide level, may influence strain-specific responses to metabolic syndrome, and confirmed that Nox4 functional missense variants were caused by SNPs in the CAST and PWK strains [ 88 ]. In future studies, we will dissect muscle transcriptome to identify candidate genes and genetic variants regulating muscle atrophy that are differentially expressed by Rg3, are associated with muscle atrophy-traits, and carry missense variants of PWK SNPs.…”
Section: Discussionmentioning
confidence: 99%
“…The MGI and Wellcome Sanger Institute provide sequencing data of most of the inbred strains, including the eight CC founder strains. As a preliminary study, we analyzed the liver transcriptomes of eight CC founder strains fed a high-fat cholesterol diet and found that the NOX4, which is associated with hepatic triglyceride and plasma trimethylamine N-oxide level, may influence strain-specific responses to metabolic syndrome, and confirmed that Nox4 functional missense variants were caused by SNPs in the CAST and PWK strains [ 88 ]. In future studies, we will dissect muscle transcriptome to identify candidate genes and genetic variants regulating muscle atrophy that are differentially expressed by Rg3, are associated with muscle atrophy-traits, and carry missense variants of PWK SNPs.…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, samples were measured in duplicate using the EnzyChrom AF HDL and LDL/VLDL Assay kit (BioAssay Systems, Hayward, CA, USA). Liver triglyceride levels were determined using the Folch extraction method, as previously described in [ 59 ]. In brief, after performing necropsy the liver of the mouse was collected, frozen, and stored at -80°C for subsequent analysis.…”
Section: Methodsmentioning
confidence: 99%
“…in fat and carbohydrates, and have proven the significant impact of the genetic background in the liver (eg liver weight, hepatic TG accumulation, ALT, expression levels), metabolic (eg body weight, fat accumulation and distribution), symbiotic (eg microbiome) and behavioural traits (eg dietary habits). 146,147 The genetic background holds significant importance as the same diet could lead to a variety of phenotypes in these mice. For instance, Busnelli et al investigated the effect of both diet and genotype on the miRNome of mice with altered lipoprotein metabolism.…”
Section: Diethylnitrosamine Model (Den)mentioning
confidence: 99%
“…Working with well‐established genetically homogeneous strains is essential in order to maximize the reproducibility of results under our experimental conditions. Several studies have tested the effects on different inbred mouse strains fed the same diet, enriched in fat and carbohydrates, and have proven the significant impact of the genetic background in the liver (eg liver weight, hepatic TG accumulation, ALT, expression levels), metabolic (eg body weight, fat accumulation and distribution), symbiotic (eg microbiome) and behavioural traits (eg dietary habits) 146,147 …”
Section: Other Additional Factors To Considermentioning
confidence: 99%